Digital Literacy, Social Media Use, and Entrepreneurial Motivation as Determinants of Entrepreneurial Decisions: The Moderating Role of Government Regulation in the Indonesian Context - Monalika, Hani Putri; Anasta, Lawe (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
In an era where digital platforms are reshaping economic participation, fostering youth entrepreneurship has become a national development imperative for Indonesia — a country with over 190 million active internet users in 2025 and an ambitious regulatory agenda targeting digital MSME growth. This study investigates the effects of digital literacy, social media use, and entrepreneurial motivation on entrepreneurial decisions among Indonesian youth, with government regulation as a moderating variable. Grounded in the Theory of Planned Behavior (Ajzen, 1991), Self-Determination Theory (Deci & Ryan, 2024), and Institutional Theory (North, 1990), the study integrates individual-level cognitive and motivational factors with macro-level institutional contexts — an approach that remains underexplored in the Indonesian digital entrepreneurship literature. A quantitative cross-sectional survey of 240 university students and alumni exposed to government entrepreneurship programs during 2020–2025 was analyzed using Moderated Regression Analysis (MRA). All three individual-level variables — digital literacy, social media use, and entrepreneurial motivation — significantly and positively predict entrepreneurial decisions. Notably, government regulation significantly moderates the relationship between digital literacy and entrepreneurial decisions, but does not moderate the effects of social media use or motivation. This null moderation for social media reflects a theoretically important boundary condition: youth social media engagement is driven more by global platform algorithms and transnational digital trends than by local bureaucratic regulations, rendering it largely impervious to domestic institutional conditions. The novelty of this study is threefold: (1) it is the first to simultaneously test three behavioral antecedents alongside a government regulation moderator within the Indonesian digital entrepreneurship context; (2) it provides empirical evidence that institutional moderation is selective — amplifying domain-congruent competencies while leaving algorithm-mediated and motivation-driven pathways unaffected; and (3) it offers a nuanced contribution to Institutional Theory by demonstrating that formal regulations do not uniformly condition all pathways to entrepreneurial decisions. These findings provide evidence-based guidance for policymakers seeking to align digital literacy programs with enabling regulatory frameworks to stimulate youth entrepreneurship in Indonesia.